2020
DOI: 10.1136/bmjopen-2019-034018
|View full text |Cite
|
Sign up to set email alerts
|

Core outcome set for studies on pregnant women with vasa previa (COVasP): a study protocol

Abstract: IntroductionVasa previa is a condition where fetal blood vessels run unprotected in the membranes, outside the umbilical cord, and cross the internal opening of the cervix. During rupture of membranes, these vessels can rupture and put the baby at serious risk of severe blood loss and death. Numerous studies are being conducted to improve diagnostic modalities and establish clear management plans to improve pregnancy outcomes. However, the lack of a standardised set of outcomes for studies on vasa previa makes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…19,22,38 The quality of included studies with respect to their measurement properties was not assessed, in accordance with some of the most recently published research on COS development. 39,40 This decision was made due to the lack of well-validated quality assessment tools designed to assess measurement properties of included studies 27 and the fact that descriptors of reporting quality are not considered integral components of the review stage for COS development. 39 3 | RESULTS…”
Section: Discussionmentioning
confidence: 99%
“…19,22,38 The quality of included studies with respect to their measurement properties was not assessed, in accordance with some of the most recently published research on COS development. 39,40 This decision was made due to the lack of well-validated quality assessment tools designed to assess measurement properties of included studies 27 and the fact that descriptors of reporting quality are not considered integral components of the review stage for COS development. 39 3 | RESULTS…”
Section: Discussionmentioning
confidence: 99%
“… 10 Patient and stakeholder interviews which enable researchers to obtain first-hand information from those directly affected by a condition and proposed interventions, and about how they would prioritize outcomes while making medical decisions, have therefore been the focus of recent publications. 15 , 16 , 17 , 18 While conducting these interviews, in keeping with the primary intention of eliciting outcomes, attention must be paid to the use of a semistructured interview guide and the liberal use of prompts to redirect patients and family members to focus on outcomes. Interpretive analysis, wherein quotes, anecdotes, experiences, and perceptions are translated into measurable outcomes, forms an integral part of the research process, especially for patient interviews, as the concept of outcomes can be difficult to explain and discuss with those who do not work and think in a health intervention context.…”
Section: Discussionmentioning
confidence: 99%
“…As the aim of this scoping review is to identify all reported outcomes in order to generate a long list of outcomes to inform the development of the COS, and there is no validated tool to assess the quality of outcome reporting, it is decided that the quality of outcome reporting of included studies would not be assessed [ 22 ].…”
Section: Methodsmentioning
confidence: 99%